A study on spleen transient elastography in predicting the degree of esophageal varices and bleeding. Issue 9 (March 2019) - Wang, Xie-Kui; Wang, Ping; Zhang, Yong; Qi, Sheng-Lin; Chi, Kun; Wang, Gong-Chen
Abstract : Abstract: This study aims to investigate the value and determine the accuracy of spleen stiffness in predicting the degree of esophageal varices and bleeding in patients with liver cirrhosis. The age, gender, liver stiffness, spleen stiffness, and gastroscopy results of 124 inpatients or outpatients with liver cirrhosis and healthy volunteers, who underwent both gastroscopy and FibroScan testing in the fasting state, were retrospectively analyzed. According to the gastroscopy results, the patients and healthy volunteers were divided into six groups: varicose bleeding, severe varices, moderate varices, mild varices, no varices, and healthy control group. Then, the receiver operating characteristic curves were drawn, and the corresponding area under each curve was calculated and evaluated to predict the severity of varices based on the relevance of the area and its parameters. The area under the receiver operating characteristic curve of liver stiffness and spleen stiffness for predicting severe and moderate varices in the bleeding group was 0.955 and 0.989, respectively. The cut-off values were 29.6 kPa and 45.5 kPa, respectively. The area under the receiver operating characteristic curve of liver stiffness for predicting varicose bleeding was 0.860 (95% CI: 0.789–0.931). The liver stiffness cut-off value for predicting varicose bleeding was 33.2 kPa, with a specificity and sensitivity of 66.02% and 95.24%, respectively. The area under the receiver operating characteristic curve of spleen stiffness for predicting varicose bleeding was 0.923 (95% CI: 0.875–0.971). A spleen stiffness cut-off value of 55.2 kPa had a sensitivity and specificity of 90.48% and 86.41%, respectively. Spleen stiffness can predict the degree of esophageal varices and bleeding in liver cirrhosis patients, and has good predictive accuracy.